The Criteria and Principles of Investigation of Economic Activity (On Different Levels of Theoretical Interpretation) - Buračas, Antanas (Problemos, 1977)
The criteria of economic and noneconomic, productive and nonproductive activity are not always realised consistently (as a result of difficulties when measuring the products of domestic sector, etc.). The article points out to the fact that this results in incorrect determination of macroeconomic quantities and proportions. The article emphasizes the inversion and transformation of economic methodology on different levels of theoretical interpretation, e.g., specific features of dichotomy between reistical and social, stocks and flows approaches and so on. Logical and time discursiveness of value hierarchies as well as the commensurability between the latter and means of their realisation in socioeconomic activity are also pointed out.